PENINGKATAN KUALITAS PENDIDIKAN MELALUI PENERAPAN MANAJEMEN STRATEGI - Andikarya, Oke; Muluk, Kiki Abdul (Universitas Insan Cendekia Mandiri, 2025)
The review aims to determine the improvement of educational management through the implementation of strategic management. The review method used is literature, by collecting various article references, supporting international and national journals. The results of the study in the form of articles, describe a significant increase in the quality of education in well-managed universities. Universities that are not supported by good management processes can cause irregular organizational rhythms so that they fail to achieve educational goals properly. Improving the quality of education has an impact on graduates from these universities. Through strategic management, future opportunities can be expanded and realized risks can be minimized. Strategic management can be achieved if all parties directly interested in universities, such as university administrators, parents of students, lecturers and staff, are involved. directly